Self-respecting worker in the gig economy: A dynamic principal-agent model - Zsolt Bihary; Péter Csóka; Péter Kerényi; Alexander Szimayer (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
We introduce a dynamic principal-agent model to understand the nature of contracts between an employer and an independent gig worker. We model the worker's self-respect with an endogenous participation constraint; he accepts a job offer if and only if its utility is at least as large as his reference value, which is based on the average of previously realized wages. If the dynamically changing reference value capturing the worker's demand is too high, then no contract is struck until the reference value hits a threshold. Below the threshold, contracts are offered and accepted, and the worker's wage demand follows a stochastic process. We apply our model to different labor market structures and investigate first-best and second-best solutions. We show that a far-sighted employer may sacrifice instantaneous profit to regulate the agent's demand. Employers who can afford to stall production due to a lower subjective discount rate will obtain higher profits. Our model captures the worker's bargaining power by a vulnerability parameter that measures the rate at which his wage demand decreases when unemployed. With a low vulnerability parameter, the worker can afford to go unemployed and need not take a job at all costs. Conversely, a worker with high vulnerability can be exploited by the employer, and in this case our model also exhibits self-exploitation.
Keywords: C73; D82; D86; J33; J41; 330; Contingent work; vulnerability; contract theory; stochastic control theory; endogenous participation constraint